Microcephaly, Short Stature, Intellectual Disability, Speech Absence and Cataract Are Associated with Novel Bi-Allelic Missense Variant in RTTN Gene: A Seckel Syndrome Case Report - Behjat Ul Mudassir; Zehra Agha (MDPI AG, 2023)
The RTTN gene encodes centriole biogenesis, replication, symmetry and cohesion, basal body organization and has recently been associated with the appearance of microcephaly syndromes. RTTN-related neurological defects including microcephaly, intellectual disability, congenital dwarfism, ophthalmic manifestations, and epilepsy are mainly due to abnormal brain development pathways and loss-of-function protein mutations. We present a consanguineous Pakistani family clinically suspected of Seckel syndrome with severe microcephaly, severe intellectual disability, short stature, absence of speech, pointed nose, narrow face and bilateral cataract in two siblings residing in the suburbs of Islamabad. Forty cases of Seckel syndrome have been reported to date in the literature due to mutations in the ATR, TRAIP, RBBP8, NSMCE2, NIN, CENPJ, DNA2, CEP152 and CEP63  genes. The objective of the study was to perform a clinical diagnosis, genetic analysis, and pathophysiology of Seckel syndrome in the proband. Whole-exome sequencing discovered NM_173630.4: c.57G > T(pGlu19Asp) missense variant in exon 2 of the RTTN gene that co-segregates in the family. This novel variant, to the best of our knowledge, is pathogenic and with autosomal recessive inheritance expressed as Seckel syndrome in the affected members of the family. The present study has expanded the genetic knowledge of novel RTTN gene variants associated with Seckel syndrome and has broadened its phenotype spectrum in the Pakistani population, which comprises diverse ethnicities. We hope that our study will open new horizons for individual molecular diagnosis and therapeutics to improve the life of patients with this congenital syndrome.